Cyber security for microgrids - Sahoo, Subham; Blaabjerg, Frede; Dragičević, Tomislav (IET energy engineering series ;, 2022)
Microgrids use ICT to intelligently deliver energy and integrate clean generation. They can operate independently from a larger grid and can help to strengthen grid resilience. Applications include remote as well as urban areas, hospitals, and manufacturing complexes. Cybersecurity challenges arise, exposing the microgrids to cyber-attacks, possibly resulting in harm to infrastructure and to people. Research has classified attacks based on confidentiality, integrity, and availability, and most countermeasures focus on specific attacks or on protecting specific components. A global approach is needed combining solutions that can secure the entire system and respond in milliseconds. This reference work for researchers, in academia, industry and at grid operators as well as for students, provides an up-to-date framework for cybersecurity technologies and perspectives on operation, control, testbed and protection of microgrids from a system level perspective. Coverage includes the role of modern power electronics in active distribution networks, cyber-induced steady-state and dynamic issues, situational awareness of cyber-attacks, AI aided detection of data manipulation, cyber security threats in multi-agent microgrids, communication assisted protection, design and modeling of cyber-attacks for grid tied PV systems, stealth cyber-attacks, resilient distributed control, cyber-physical testbeds for smart grids and EV charging, and event-driven resiliency of microgrids against cyber-attacks. The book offers advanced cyber-attack detection strategies for microgrids to address breaches, counter attacks, deploy appropriate countermeasures, and stabilize microgrids under cyber-attacks.